Paul and Socrates in Dialogue: Points of Contact between the Areopagus Speech and the Apology - Cowan, J. Andrew (New Testament studies, 2021)
For many years, scholars have noted striking similarities between the account of Paul's visit to Athens in Acts and ancient accounts of the trial of Socrates. There have been at least five distinct proposals about the significance of these similarities, but each has substantial shortcomings. In this article, I argue that Luke's purpose is to place Paul's Areopagus speech in dialogue with the thought of Socrates as it is represented in traditions about his trial, especially Plato's Euthyphro and Apology.